PENGARUH LINGKUNGAN KERJA PADA LOYALITAS KARYAWAN DENGAN KINERJA KARYAWAN SEBAGAI VARIABEL MEDIASI : Studi Kasus Pada Proyek Check Dam Ahuru Kota Ambon - Sitti Rahma Rumadaul; Muhammad Mathori (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study discusses how the work environment and employee loyalty with employee performance as a mediating variable for the Ahuru Check Dam project in Ambon City, Maluku, Indonesia. The purpose of this study was to test and analyze whether the influence of the work environment on employee loyalty and employee performance as a mediating variable in the Rinjani Way Batu Merah upgrading project, Ambon City, Maluku, Indonesia. The analytical test tool used is SmartPLS v.3.0.0 with the SEM (Structural Equation Modeling) analysis method. The results of the study show that the work environment has no effect on employee performance. Employee performance has a positive and significant effect on employee loyalty. The work environment has a positive and significant effect on employee loyalty and employee performance acts as a mediating variable in the work environment in a positive and significant way on employee loyalty.